INCLUSIVE EDUCATION: STRATEGIES AND IMPACT ON CONTEMPORARY SOCIETY - Joaquina de Borba, Nara; Adriana Santin Ferreira, Vanderleia; Palhares dos Santos, Tainara; Carvalho, Shalline (Revista Gênero e Interdisciplinaridade, 2024)
Inclusive education is an educational model that aims to ensure the access and participation of all students, regardless of their individual characteristics, such as disabilities, ethnic, socioeconomic, or cultural backgrounds. It promotes pedagogical practices that recognize and value diversity, aiming for meaningful learning for all students. The concept of inclusive education has evolved over the years, moving beyond simply integrating students with disabilities into schools. It now encompasses the promotion of educational environments that value the diversity and individuality of each student, regardless of their personal characteristics. This implies curriculum adaptations, specialized support, and actions to ensure that all students have equal access to learning and development opportunities.